2013
DOI: 10.15835/nbha4119009
|View full text |Cite
|
Sign up to set email alerts
|

Heat-stress Tolerance of Some Strawberry (Fragaria × ananassa) Cultivars

Abstract: Physiological parameters were used to investigate genotypic variations in 15 strawberry cultivars [‘Aromas’, ‘Camarosa’, ‘Carmine’, ‘Cal. Giant 3’ (CG3), ‘Cal. Giant 5’ (CG5), ‘Elsanta’, ‘Fern’, ‘Festival’, ‘Honeoye’, ‘Kabarla’, ‘Redlands Hope’ (R.Hope), ‘Ruby Gem’, ‘Selva’, ‘Sweet Charlie’ and ‘Whitney’] and their relationship to heat-stress tolerance (HST). Cold stored (frigo) strawberry seedlings were grown in pots for six weeks and then transferred to a growth chamber. The temperature in the growth chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
(33 reference statements)
3
16
0
2
Order By: Relevance
“…The HS exhibited a negative effect on all studied faba bean genotypes. The observed decrease in growth parameters (PH, Shoot FW and DW, leaf area) with increasing levels of temperature over the control may be due to the loss of turgidity and RWC (Table 2) (Kesici et al, 2013). The high level of temperature stress might be altered cell division and cell elongation resulted in reduced leaf area in all genotypes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The HS exhibited a negative effect on all studied faba bean genotypes. The observed decrease in growth parameters (PH, Shoot FW and DW, leaf area) with increasing levels of temperature over the control may be due to the loss of turgidity and RWC (Table 2) (Kesici et al, 2013). The high level of temperature stress might be altered cell division and cell elongation resulted in reduced leaf area in all genotypes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There are wider variations in strawberry cultivars in terms of their response to abiotic stress . Cultivars Elsanta, Redlans Hope and Camarosa were found to be tolerant to high temperature whereas cultivars Festival, Whitney, Fern and Cal Giant3 cultivars were sensitive . Elsanta cultivar was reported as more sensitive to salinity stress than Korona cultivar .…”
Section: Introductionmentioning
confidence: 98%
“…Kesici et al (2013) reported on the heat stress tolerance of 15 strawberry cultivars (' Aromas' , 'Camarosa' , 'Carmine' , 'Cal. Giant 3' , 'Cal.…”
Section: Introductionmentioning
confidence: 99%